2018
DOI: 10.7567/jjap.57.04fr15
|View full text |Cite
|
Sign up to set email alerts
|

Hole trapping in SiC-MOS devices evaluated by fast-capacitance–voltage method

Abstract: We demonstrated a fast-capacitance-voltage (CV) method for the evaluation of the number and location of holes trapped in a 4H-SiC MOS device under negative gate bias stress. The number of trapped holes was carefully estimated by suppressing recombination and detrapping during stress relaxation. It was found that a large number of holes trapped in a short stress time were reduced by nitridation, and that the hole trapping in a longstress-time region was accelerated by increases in temperature and electric field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Many studies reported on the Vth instability upon negative gate bias stress on MOSFETs [9, 52,70]. However, to get insights on the basic trapping mechanisms of NIOTs in the insulator, it is useful to analyse the behaviour of p-type MOS capacitors ( Figure 11) [71]. Figure 11 shows a comparison of different techniques to determine the shift ΔVth in MOSFETs (current measurements) and the flat band voltage shift ΔVFB in MOS capacitors (capacitance measurements).…”
Section: Charge Trapping Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported on the Vth instability upon negative gate bias stress on MOSFETs [9, 52,70]. However, to get insights on the basic trapping mechanisms of NIOTs in the insulator, it is useful to analyse the behaviour of p-type MOS capacitors ( Figure 11) [71]. Figure 11 shows a comparison of different techniques to determine the shift ΔVth in MOSFETs (current measurements) and the flat band voltage shift ΔVFB in MOS capacitors (capacitance measurements).…”
Section: Charge Trapping Phenomenamentioning
confidence: 99%
“…∆V FB (equivalent to ∆V th ) as a function of the stress time measured with different electrical characterization techniques. Data taken from Reference[71].…”
mentioning
confidence: 99%
“…16,17) On the other hand, NO-POA degrades the threshold voltage stability through enhanced hole trapping. [18][19][20] We previously reported that N atoms are preferentially introduced into the SiC side of the SiO 2 /SiC interface in the initial stage of NO-POA; then, they are distributed on the SiO 2 side as nitridation proceeds. 21,22) Considering that SiN film is used as a charge-trapping layer in current nonvolatile memory devices, 23) we expect that the threshold voltage stability could be improved by selectively removing N atoms distributed on the SiO 2 side.…”
mentioning
confidence: 99%
“…Besides the initial performance of SiC-MOS devices, long-term reliability related to for example, the threshold voltage (V th ) shift due to carrier trapping near the SiO 2 =SiC interfaces, is a crucial issue. Although the advantages and drawbacks of interface nitridation were previously reported, 27,28) details about the relationship between the interface structure and electrical properties have not been explored yet.…”
mentioning
confidence: 99%
“…Actually, in addition to the mobility degradation, the harmful impact of NO-POA on the long-term reliability of SiC-MOSFETs on Si-face substrates has been reported. 27,28) Although the as-oxidized device without NO-POA showed a significant V th shift even for a short stress time and a rapid V th shift was proven to be suppressed by NO-POA, the long-term V th reliability of the NO-treated device severely deteriorated with increasing stress time. Considering the correlation between these reports and the nitrogen depth profiles shown in Fig.…”
mentioning
confidence: 99%